Pathogenicity study of extracellular proteins (ECPs) and cellular membrane proteins (CMPs) of Streptococcus agalactiae and its effect as immunomodulator in African catfish (Clariasgariepinus) - Mat Yunus, Nor Aniskiha (2016)
Cellular Membrane Proteins (CMPs) are bacterial surface proteinsthat could be a source of immunogens while the Extracellular protein (ECPs) are bacterial secretory products that able to activate host‟simmune response. However, there is lack of previous studies done to evaluate the immune response of catfish against ECPs and CMPs using AGPT. This study aimed to evaluate the in vivo effect of the ECPs and CMPs of Streptococcus agalactiae on pathogenicity and immunity of the African catfish (Clariasgariepinus) fingerlings.The ECPs and CMPs of S.agalactiae were intraperitoneally (i.p) injected into African catfish fingerlings to determine whether the bacteria products able to cause disease and also stimulate fish‟s immune response. Bacteria cells from pure culture were harvested by centrifugation at 1800xg for 15 minutes to separate ECPs and CMPs from bacteria suspension. Serial dilutions for ECPs and CMPs were done to give 10-1, 10-2, 10-3, 10-4, and 10-5 diluents. The morbidity, cumulative mortality and percentage survivability of the fish were recorded within 7dpi. Pooled serum samples from fingerlings of each dilution of ECPs and CMPs injected fish as well as control group were taken via caudal peduncle vein at 8th dpi. Clinical signs observed include anorexia, lethargy, erratic swimming, corneal opacity and exopthalmia. The sera were tested for antibody production by Agar Gel Precipitation Test (AGPT). Results showed that CMPs was more virulence than ECPs based on mortality, however, statistically there was no significance difference between the fingerlings injected with ECPs and CMPs at p<0.05. Results also showed that there was no significant difference between the dilutions of the inocula and the percentage survivability of fingerlings for both ECPs and CMPs. Serum analysis via AGPT showed negativity for all ECPs and CMPs indicating that there was no antigen-antibody complex formed for every dilution.